Nano-enzyme, preparation method thereof and application of nano-enzyme in antibiosis

A 3nm copper-cobalt nanozyme, prepared by a simple method, effectively inhibits both Gram-negative and Gram-positive bacteria by decomposing hydrogen peroxide, addressing the need for a stable and economical antibacterial material to combat antibiotic-resistant bacteria.

CN119237724APending Publication Date: 2025-01-03ANHUI NORMAL UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411252877.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-09
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The long-term use and abuse of antibiotics have accelerated bacterial resistance, making it crucial to find an effective antibacterial material that can replace antibiotics and address complex bacterial infections, while natural enzymes are expensive, unstable, and difficult to produce.

Method used

A nanozyme with a 3nm average particle size, composed of copper-cobalt nanoparticles, is prepared by mixing copper chloride and cobalt chloride solutions with ascorbic acid and sodium hydroxide, exhibiting peroxidase-like activity and inhibiting both Gram-negative and Gram-positive bacteria with minimum inhibitory concentrations of 22.5μg/mL for Escherichia coli and 5.63μg/mL for Staphylococcus aureus.

Benefits of technology

The copper-cobalt nanozyme is low-cost, stable, and effective in decomposing hydrogen peroxide to produce hydroxyl radicals, causing bacterial death, offering a stable and economical alternative to natural enzymes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119237724A_ABST
    Figure CN119237724A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of nano-enzyme preparation and application thereof, in particular to nano-enzyme and a preparation method and application thereof in antibiosis, the nano-enzyme is prepared by using ascorbic acid, sodium hydroxide, copper chloride and cobalt chloride as reaction raw materials and adopting a liquid-phase chemical reduction coprecipitation method, and copper-cobalt nano-enzyme is obtained. The diameter of the prepared nano-material is about 3 nm, the nano-material has good peroxidase-like activity, when a substrate hydrogen peroxide is catalyzed, the Michaelis constant KM is 0.93 mM, the maximum reaction rate Vmax is 12.1862 * 10 <-8 > (M.s <-1 >), the mimic enzyme shows good antibacterial performance on escherichia coli and staphylococcus aureus, the bactericidal effect can be achieved by breaking cell walls, and the mimic enzyme has good application prospects. And the minimum inhibitory concentrations of the compounds are respectively 22.5 [mu] g / mL and 5.63 [mu] g / mL. The nano enzyme is simple in preparation method, low in cost and remarkable in antibacterial effect, and has wide application prospects in the fields of medical industry, chemical production and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a nanozyme and a preparation method thereof and application thereof in antibacterial treatment, belonging to the technical field of nanozyme preparation and application thereof. Background Art

[0002] Bacterial infection has many harmful effects on the human body, including tissue damage, immune system response, and other complications that may be caused. Therefore, it has always been a safety issue faced by people. The use of antibiotics is an effective means of treating bacterial infections. However, the long-term use and abuse of antibiotics and other drugs have greatly accelerated the process of bacterial resistance. More and more bacteria have gradually developed from sensitive bacteria to super bacteria that are resistant to multiple antimicrobial drugs. At the same time, antibiotics can also enter the human body through the food web, threatening human health and safety. Bacterial resistance has become one of the most pressing health threats in the world. Therefore, it is particularly important to find an antibacterial material that can replace antibiotics to cope with increasingly complex and stubborn bacterial infectious diseases.

[0003] In recent years, copper-based compounds in nanozymes have great application potential in biomedicine, chemical production and other fields. Copper, as a bioactive element, has many advantages, such as copper has a broad spectrum of antibacterial activity, and has killing and inhibitory effects on a variety of microorganisms such as bacteria, fungi and viruses. The antibacterial and sterilization mechanisms of copper are diverse: bacteria are not easy to form a protective biofilm on the copper surface. When copper comes into contact with microorganisms, copper ions will be released and enter the microbial cells, interfering with their metabolism and biochemical reactions, leading to the death of microorganisms. In addition, copper can also directly interact with proteins and DNA on the surface of microorganisms to destroy their structure and function. This rapid bactericidal property of copper makes it impossible for microorganisms to develop copper resistance. Therefore, copper is a very promising alternative material for antibiotics. Cobalt is an extremely important life element in life sciences and an essential trace element in organisms. Cobalt ions are found in the active centers of hydrogenase, carbon monoxide dehydrogenase and urease. Cobalt has potential application value in many fields such as chemistry, biology, and medicine.

[0004] Organisms can use their own catalysts to inhibit the growth of bacteria. For example, natural peroxidase (POD) and oxidase (OXD) in living bodies can catalyze substrates to produce reactive oxygen species (ROS) to resist bacterial invasion. Therefore, enzymes have become the preferred alternative to antibiotics due to their high catalytic activity, but natural enzymes are expensive, easy to inactivate, and have a complex production process, which hinders their application in antibacterial applications. Nanozymes are a type of nanomaterial with enzyme catalytic activity, which can be divided into two categories: one is to modify natural enzymes or groups with enzyme catalytic activity on nanomaterials, and the nanomaterials act as carriers; the other is that the nanomaterials themselves have enzyme-like catalytic activity. As a new generation of artificial enzymes, nanozymes have unique performance advantages of nanomaterials such as simple preparation, good stability, and low cost compared to natural enzymes. They have great potential in the fields of bactericidal and anti-inflammatory, cancer treatment, and packaging materials. Summary of the invention

[0005] In view of the deficiencies in the prior art, the object of the present invention is to provide a nanozyme and a preparation method thereof and an application in antibacterial treatment to solve the problems raised in the above-mentioned background technology.

[0006] In order to achieve the above-mentioned object, the present invention is implemented through the following technical scheme: a nanozyme, wherein the average particle size of the nanozyme is 3nm.

[0007] Specifically, when the nanozyme catalyzes the substrate hydrogen peroxide, the Michaelis constant K M is 0.93 mM, and the maximum reaction rate Vmax is 12.1862×10 -8 (M·s -1 ).

[0008] A method for preparing a nanozyme, the nanozyme preparation process is as follows: first, a copper chloride solution and a cobalt chloride solution are mixed, then, an ascorbic acid solution and a sodium hydroxide solution are mixed and stirred, the prepared mixed solution is quickly added dropwise to the mixed solution of copper chloride and cobalt chloride and shaken to mix, and the reaction is carried out at room temperature to finally form a clear and transparent green solution, that is, the copper-cobalt nanozyme.

[0009] Specifically, the mass volume ratio of the copper chloride solution to the cobalt chloride solution is (1-4): 1, mg / mL.

[0010] Specifically, the concentrations of the copper chloride solution and the cobalt chloride solution are 1-10 mg / mL and 1-10 mg / mL, respectively.

[0011] Specifically, the concentration of the sodium hydroxide solution is 10-60 mg / mL, and the concentration of the ascorbic acid solution is 1-4 mg / mL.

[0012] Specifically, the mixed reaction temperature is 15-30°C, the time is 2-3h, and the rotation speed is 500rpm. Specifically, it has an inhibitory effect on both Gram-negative bacteria and Gram-positive bacteria, wherein the minimum inhibitory concentration for Escherichia coli among Gram-negative bacteria is 22.5μg / mL, and the minimum inhibitory concentration for Staphylococcus aureus among Gram-positive bacteria is 5.63μg / mL.

[0013] Specifically, the bacteria include but are not limited to Escherichia coli and Staphylococcus aureus.

[0014] Specifically, the nanozyme is used in the pharmaceutical industry and chemical production fields.

[0015] Beneficial effects of the present invention:

[0016] Compared with natural enzymes, the provided antibacterial composite nanozyme is low-cost, highly stable, and easy to produce. Its raw materials are economical and easily available, simple to prepare, and highly stable. It still has good antibacterial effect after standing for one month. It can decompose hydrogen peroxide to produce hydroxyl radicals and then destroy the bacterial structure and cause bacterial death. The preparation of copper-cobalt nanozymes broadens the potential path for the rational design of effective copper-based nanozymes and provides a new method for understanding the antibacterial effect of nanoparticles. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Other features, objects and advantages of the present invention will become more apparent from the detailed description of non-limiting embodiments made with reference to the following drawings:

[0018] Figure 1 Transmission electron microscopy image of copper-cobalt nanozyme;

[0019] Figure 2 Optimization diagram of the amount of sodium hydroxide added in the synthesis of copper-cobalt nanozymes;

[0020] Figure 3 Optimal pH diagram of copper-cobalt nanozymes;

[0021] Figure 4 Thermal stability diagram of copper-cobalt nanozymes;

[0022] Figure 5 Experimental diagram of the inhibition zone of Escherichia coli treated with copper-cobalt nanozymes;

[0023] Figure 6 Experimental diagram of the inhibition zone of Staphylococcus aureus treated with copper-cobalt nanozymes;

[0024] Figure 7 Growth curve of Escherichia coli treated with different concentrations of copper-cobalt nanozymes;

[0025] Figure 8 Growth curve of Staphylococcus aureus treated with different concentrations of copper-cobalt nanozymes;

[0026] Fig. 9 Scanning electron micrograph of Escherichia coli treated with copper-cobalt nanozymes (a is the control group, b is the experimental group);

[0027] Fig.10 Scanning electron micrograph of Staphylococcus aureus treated with copper-cobalt nanozymes (a is the control group, b is the experimental group);

[0028] Fig.11 Transmission electron micrograph of Escherichia coli treated with copper-cobalt nanozymes (a is the control group, b is the experimental group);

[0029] Fig.12 Transmission electron microscopy images of Staphylococcus aureus treated with copper-cobalt nanozymes (a is the control group, b is the experimental group). DETAILED DESCRIPTION

[0030] In order to make the technical means, creative features, objectives and effects achieved by the present invention easy to understand, the present invention is further explained below in conjunction with specific implementation methods.

[0031] See also Figures 1 to 12 The present invention provides a technical solution: a nanozyme, wherein the average particle size of the nanozyme is 3 nm.

[0032] When nanozymes catalyze the substrate hydrogen peroxide, the Michaelis constant K M is 0.93 mM, and the maximum reaction rate Vmax is 12.1862×10 -8 (M·s -1 ).

[0033] A method for preparing a nanozyme, the nanozyme preparation process is as follows: first, a copper chloride solution and a cobalt chloride solution are mixed, then, an ascorbic acid solution and a sodium hydroxide solution are mixed and stirred, the prepared mixed solution is quickly added dropwise to the mixed solution of copper chloride and cobalt chloride and shaken to mix, and the reaction is carried out at room temperature to finally form a clear and transparent green solution, that is, the copper-cobalt nanozyme.

[0034] The mass volume ratio of the copper chloride solution to the cobalt chloride solution is (1-4):1, mg / mL, wherein the optimal mass volume ratio of the copper chloride solution to the cobalt chloride solution is 1:1, mg / mL.

[0035] The concentrations of the cupric chloride solution and the cobalt chloride solution are 1-10 mg / mL and 1-10 mg / mL respectively, and the optimal concentrations of both are 2.1 mg / mL.

[0036] The concentration of the sodium hydroxide solution is 10-60 mg / mL, and the concentration of the ascorbic acid solution is 1-4 mg / mL, wherein the optimal concentrations are 16 mg / mL and 2 mg / mL, respectively.

[0037] The mixed reaction temperature is 15-30°C, the time is 2-3h, and the rotation speed is 500rpm. The optimal reaction temperature is 27°C and the reaction time is 2h.

[0038] It has inhibitory effects on both Gram-negative and Gram-positive bacteria, with the minimum inhibitory concentration for Escherichia coli among Gram-negative bacteria being 22.5 μg / mL, and the minimum inhibitory concentration for Staphylococcus aureus among Gram-positive bacteria being 5.63 μg / mL.

[0039] Bacteria include, but are not limited to, Escherichia coli and Staphylococcus aureus.

[0040] Nanozymes are used in the pharmaceutical industry and chemical production.

[0041] The prepared copper-cobalt nanozyme has peroxidase-like activity. When the nanozyme catalyzes the substrate hydrogen peroxide, the Michaelis constant K calculated by the double reciprocal method is M is 0.93 mM, and the maximum reaction rate Vmax is 12.1862×10 -8 (M·s -1 ); When the substrate is 3,3',5,5'-tetramethylbenzidine (TMB), the Michaelis constant K M is 0.087 mM, and the maximum reaction rate is 3.8582×10 -6 (M·s -1 ).

[0042] Example 1 Preparation of Copper-Cobalt Nanozyme 1

[0043] ① Mix 2 mL of 2 mg / mL ascorbic acid and 325 μL of 16 mg / mL sodium hydroxide to mix them thoroughly; ② Mix 3 mL of copper chloride solution and cobalt chloride solution in equal proportions, and the concentrations of copper chloride solution and cobalt chloride solution are both 2.1 mg / mL; ③ Quickly add the mixed solution prepared in step ① dropwise to the solution prepared in step ②, and immediately shake and mix; ④ Stir the mixed solution at 27° C. for 2 h at a rotation speed of 500 rpm to obtain the nanozyme, copper-cobalt nanoparticles (CuCoNPs) of the present invention.

[0044] Example 2 Preparation of Copper-Cobalt Nanozyme 2

[0045] According to the preparation method of Example 1, only the concentration of sodium hydroxide in step ② was adjusted, and the other conditions remained unchanged to obtain copper-cobalt nanozyme.

[0046] Analysis of kinetic parameters of copper-cobalt nanozymes

[0047] Take 5 EP tubes, add 3,3',5,5'-tetramethylbenzidine (TMB) with concentrations of 0.01mM, 0.13mM, 0.19mM, 0.26mM, and 0.31mM, respectively, add H2O2 and nanozyme to make the final concentrations of 0.4mM and 36μg / mL, respectively, react for 10min, and measure the absorbance OD at a wavelength of 650nm using a UV spectrophotometer 650 ; As above, H2O2 with concentrations of 0.04mM, 0.13mM, 0.19mM, 0.24mM, and 0.31mM were added respectively, and finally 3,3',5,5'-tetramethylbenzidine (TMB) and nanozyme were added. As shown in Table 1, when the substrate is 3,3',5,5'-tetramethylbenzidine, the Michaelis constant K calculated by the double reciprocal method M is 0.087mM, and the maximum reaction rate Vmax is 3.8582×10 -6 (M·s -1 ); When the substrate is H2O2, the Michaelis constant K M is 0.93mM, and Vmax is 12.1862×10 -8 (M·s -1 ), which shows that copper-cobalt nanozymes have strong enzyme binding ability.

[0048] Table 1 Kinetic parameters of copper-cobalt nanozymes

[0049]

[0050] Optimal pH of copper-cobalt nanozymes

[0051] 25 μL of 5 mM TMB solution and 10 mM H2O2 solution of equal volume were mixed, 3 mL of PBS solution of different pH values ​​were added to change the pH value of the solution, and finally 200 μL of copper-cobalt nanozyme was added to react for 10 min, and the OD was measured under a UV spectrophotometer. 650 ,like Figure 3 When the pH is 7.0, the activity of copper-cobalt nanozyme is the highest. Therefore, when the copper-cobalt nanozyme detects TMB as the substrate, the optimal pH is 7.0.

[0052] Thermal stability determination of copper-cobalt nanozymes

[0053] 25 μL of 5 mM TMB solution and 10 mM H2O2 solution of equal volume were mixed, 3 mL PBS (pH = 7.0) was added to change the solution pH, and finally 200 μL of copper cobalt nanozymes of different concentrations were added and reacted for 10 min. The OD was measured under a UV spectrophotometer. 650 ,like Figure 4 , nanozymes are insensitive to temperature changes, so nanozymes have high thermal stability.

[0054] Detection of the inhibitory effect of copper-cobalt nanozymes on Escherichia coli

[0055] The frozen (-80°C) Escherichia coli (Gram-negative bacteria) was taken out and inoculated onto LB solid culture medium by streaking on a plate. The streaked plate was placed in a constant temperature incubator at 37°C for overnight culture. Take two test tubes, use an inoculation loop to pick single colonies from the two plates and inoculate them into test tubes containing 5mL LB liquid culture medium, place them in a constant temperature shaker at 37°C for overnight culture, mix the bacterial solution with nanozymes at concentrations of 90μg / mL, 22.5μg / mL, and 5.63μg / mL at a 1% inoculation rate, and culture in a shaker at 37°C, 180rpm. After 12 hours, observe the turbidity of the culture solution; each experimental group was repeated 3 times independently; Escherichia coli without nanozyme was used as a blank control. When the nanozyme concentration was 90μg / mL and 22.5μg / mL, the turbidity of the culture solution was low, and when the nanozyme concentration was 5.63μg / mL, the turbidity of the culture solution was high. Therefore, copper-cobalt nanozyme has an inhibitory effect on Escherichia coli.

[0056] Add the E. coli liquid to 100 mL of warm solid culture medium and mix well. Pour it quickly into 3 culture media. After cooling, place 4 Oxford cups in each and press lightly to make them in close contact. Dilute the material with sterile liquid LB culture medium to a final concentration of 60 μg / mL, 30 μg / mL, and 15 μg / mL. Use the first Oxford cup as a control, and absorb 200 μL of the material dilution solution for the other 3 cups. After adding, place the plate in the clean bench and blow for 10 minutes, then cover the plate and place it in an incubator at 37°C for incubation. Observe the experimental phenomenon after 12 hours, measure the size of the inhibition zone with a vernier caliper, and record the experimental results. Perform 3 parallel experiments for each experimental group.

[0057] The results are as follows Figure 5 As shown in the inhibition zone experiment, treating Escherichia coli with copper-cobalt nanozymes can inhibit bacterial growth. For Escherichia coli, the inhibition diameter increases with the increase of the concentration of the copper-cobalt complex material. When the material concentration is 60μg / mL, 30μg / mL, and 15μg / mL, the inhibition zone diameter is 12mm, 8mm, and 4mm.

[0058] Detection of the inhibitory effect of copper-cobalt nanozymes on Staphylococcus aureus

[0059] Take out the frozen (-80℃) Staphylococcus aureus (Gram-positive bacteria), inoculate it on the LB solid medium by streaking the plate, and place the streaked plate in a constant temperature incubator at 37℃ for overnight incubation; take two test tubes, pick single colonies from the two plates with an inoculation loop and inoculate them in 5mL of The test tubes of LB liquid culture medium were placed in a constant temperature shaker at 37°C for overnight culture; the bacterial solution was mixed with nanozymes at concentrations of 90μg / mL, 5.63μg / mL, 2.82μg / mL, and 0.36μg / mL at a 1% inoculation rate; the culture was cultured in a shaker at 37°C, 180rpm, and the turbidity of the culture solution was observed after 12 hours; each experimental group was repeated 3 times independently; Staphylococcus aureus without nanozyme was used as a blank control. When the nanozyme concentration was 90μg / mL and 5.63μg / mL, the turbidity of the culture solution was low, and when the nanozyme concentration was 0.36μg / mL, the turbidity of the culture solution was high. Therefore, copper-cobalt nanozyme also has an inhibitory effect on Staphylococcus aureus.

[0060] Add 100mL of warm solid culture medium to the Staphylococcus aureus solution and mix well. Pour it quickly into 3 culture media. After cooling, place 4 Oxford cups in each and press lightly to make them in close contact. Dilute the material with sterile liquid LB culture medium to a final concentration of 60μg / mL, 30μg / mL, and 15μg / mL. Use the first Oxford cup as a control, and absorb 200μL of the material dilution solution for the other 3 cups. After adding, place the plate in the clean bench and blow for 10 minutes, then cover the plate and place it in an incubator at 37°C for incubation. Observe the experimental phenomenon after 12 hours, measure the size of the inhibition zone with a vernier caliper, and record the experimental results. Perform 3 parallel experiments for each experimental group.

[0061] The results are as follows Figure 6 As shown in the inhibition zone experiment, the treatment of Staphylococcus aureus with copper-cobalt nanozymes can inhibit the growth of bacteria. For Staphylococcus aureus, the inhibition zone is relatively clear, and the inhibition diameter increases with the increase of the concentration of the copper-cobalt complex material. When the material concentration is 60μg / mL, 30μg / mL, and 15μg / mL, the inhibition zone diameter is 19mm, 15mm, and 13mm.

[0062] Growth curve experiment of Escherichia coli treated with different concentrations of copper-cobalt nanozymes

[0063] The diluted nanozyme was mixed with the Escherichia coli solution to make the final concentration of the nanozyme 45 μg / mL, 22.5 μg / mL, 11.25 μg / mL, 5.63 μg / mL, 2.82 μg / mL, 1.41 μg / mL, 0.71 μg / mL, and 0.36 μg / mL; 200 μL of the mixture was added to a 96-well plate, and after the 96-well plate was sealed, it was reacted in a shaker at 37°C and 180 rpm, and the OD was measured every 2 hours using an enzyme reader.600 Absorbance value, total reaction time 24h; time as the horizontal axis, OD 600 The bacterial growth curve was plotted as the vertical axis; each experimental group was repeated 6 times independently; Figure 7 In the growth curve, treatment of Escherichia coli with copper-cobalt nanozymes showed that it could inhibit bacterial growth. For Escherichia coli, when the nanozyme concentration was 45 μg / mL and 22.5 μg / mL, the reproduction of Escherichia coli was almost completely inhibited. Therefore, the minimum inhibitory concentration for Escherichia coli was 22.5 μg / mL.

[0064] Growth curve experiment of Staphylococcus aureus treated with copper-cobalt nanozymes at different concentrations

[0065] The diluted nanozyme was mixed with the Staphylococcus aureus solution to make the final concentration of the nanozyme 45 μg / mL, 22.5 μg / mL, 11.25 μg / mL, 5.63 μg / mL, 2.82 μg / mL, 1.41 μg / mL, 0.71 μg / mL, and 0.36 μg / mL; 200 μL of the mixture was added to a 96-well plate, and after the 96-well plate was sealed, it was reacted in a shaker at 37°C and 180 rpm, and the OD was measured every 2 hours using an enzyme reader. 600 Absorbance value, total reaction time 24h; time as the horizontal axis, OD 600 The bacterial growth curve was plotted as the vertical axis; each experimental group was repeated 6 times independently; Figure 8 In the growth curve, treatment of Staphylococcus aureus with copper-cobalt nanozymes showed inhibition of bacterial growth. For Staphylococcus aureus, when the nanozyme concentrations were 45 μg / mL, 22.5 μg / mL, 11.25 μg / mL, and 5.63 μg / mL, the reproduction of Staphylococcus aureus was almost completely inhibited. Therefore, the minimum inhibitory concentration for Staphylococcus aureus was 5.63 μg / mL.

[0066] Scanning electron microscopy observation of Escherichia coli treated with copper-cobalt nanozymes

[0067] Escherichia coli liquid and nanozyme (180 μg / mL) were mixed in equal volumes and incubated for 6 hours, and Escherichia coli without drug treatment was used as a blank control; the cells were collected by centrifugation (4°C, 5000 r / min, 3 min), washed twice with PBS, and then fixed for 3 h with 500 μL glutaraldehyde fixative (2.5%); after fixation, the supernatant was discarded and washed three times with PBS; dehydrated with gradient concentration ethanol; added appropriate amount of anhydrous ethanol and blown evenly, and a suitable amount was pipetted and dropped on a smooth copper sheet, dried naturally, and placed on a culture dish containing silica gel (with filter paper); observed and photographed under a scanning electron microscope; Fig. 9In the presence of copper-cobalt nanozymes, E. coli showed collapse, while normal bacteria serving as the control group remained full.

[0068] Scanning electron microscopy observation of Staphylococcus aureus treated with copper-cobalt nanozymes

[0069] The Staphylococcus aureus liquid and nanozyme (180 μg / mL) were mixed in equal volumes and incubated for 6 hours; bacteria without drug treatment were used as blank controls; the bacteria were collected by centrifugation (4°C, 5000 r / min, 3 min), washed twice with PBS, and then fixed for 3 h with 500 μL glutaraldehyde fixative (2.5%); after fixation, the supernatant was discarded and washed three times with PBS; dehydrated with gradient concentration ethanol; added appropriate amount of anhydrous ethanol and blown evenly, and a suitable amount was pipetted and dropped on a smooth copper sheet, dried naturally, and placed on a culture dish containing silica gel (with filter paper); observed and photographed under a scanning electron microscope; Fig.10 In the presence of copper-cobalt nanozymes, the surface of Staphylococcus aureus appeared cracked, while normal bacteria serving as the control group remained plump.

[0070] Transmission electron microscopy observation of Escherichia coli treated with copper-cobalt nanozymes

[0071] The steps are the same as those for the scanning electron microscopy observation of Escherichia coli treated with copper-cobalt nanozymes; after dehydration, add 1 mL of anhydrous ethanol to the centrifuge tube and blow evenly; use a pipette to draw an appropriate amount and drop it on a smooth copper sheet (full of drops), dry it naturally, observe it under a transmission electron microscope, and take a picture; Fig.11 The changes in the morphology of Escherichia coli in the presence of copper-cobalt nanozymes can also be observed intuitively using transmission electron microscopy; the transmission electron microscopy images of bacteria treated with copper-cobalt nanozymes are consistent with the scanning analysis results. The bacterial cell morphology of the blank control group is intact, while the Escherichia coli treated with copper-cobalt nanozymes undergoes morphological changes.

[0072] Transmission electron microscopy observation of Staphylococcus aureus treated with copper-cobalt nanozymes

[0073] The steps are the same as those for the SEM observation of Staphylococcus aureus treated with copper-cobalt nanozymes; after dehydration, add 1 mL of anhydrous ethanol to the centrifuge tube and blow evenly; use a pipette to take an appropriate amount and drop it on a smooth copper sheet (full of drops), dry it naturally, observe it under a transmission electron microscope, and take a picture; Fig.12 The changes in the morphology of Staphylococcus aureus in the presence of copper-cobalt nanozymes can also be observed intuitively using transmission electron microscopy; the transmission electron microscopy image of Staphylococcus aureus treated with copper-cobalt nanozymes is consistent with the scanning analysis results. The morphology of Staphylococcus aureus treated with copper-cobalt nanozymes appears to be disintegrated, while the morphology of live bacterial cells in the blank control group is intact.

[0074] Although this specification is described according to implementation modes, not every implementation mode includes only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A nanozyme, characterized in that: The average particle size of the nanozyme is 3 nm.

2. A nanozyme according to claim 1, characterized in that: When the nanozyme catalyzes the substrate hydrogen peroxide, the Michaelis constant K M is 0.93 mM, and the maximum reaction rate Vmax is 12.1862×10 -8 (M·s -1 ).

3. A method for preparing a nanozyme according to claim 1-2, characterized in that: The nanozyme preparation process is as follows: first, mix the copper chloride solution and the cobalt chloride solution, then mix the ascorbic acid solution and the sodium hydroxide solution and stir to mix well, take the above-prepared mixed solution and quickly drop it into the mixed solution of copper chloride and cobalt chloride and shake to mix well, react at room temperature, and finally form a clear and transparent green solution, that is, the copper-cobalt nanozyme.

4. The method for preparing a nanozyme according to claim 3, characterized in that: The mass volume ratio of the copper chloride solution to the cobalt chloride solution is (1-4): 1, mg / mL.

5. The method for preparing a nanozyme according to claim 3, characterized in that: The concentrations of the copper chloride solution and the cobalt chloride solution are 1-10 mg / mL and 1-10 mg / mL, respectively.

6. The method for preparing a nanozyme according to claim 3, characterized in that: The concentration of the sodium hydroxide solution is 10-60 mg / mL, and the concentration of the ascorbic acid solution is 1-4 mg / mL.

7. The method for preparing a nanozyme according to claim 3, characterized in that: The mixed reaction temperature is 15-30°C, the time is 2-3h, and the rotation speed is 500rpm.

8. The nanozyme prepared according to claims 3-7, characterized in that: It has inhibitory effects on both Gram-negative and Gram-positive bacteria, with the minimum inhibitory concentration for Escherichia coli among Gram-negative bacteria being 22.5 μg / mL, and the minimum inhibitory concentration for Staphylococcus aureus among Gram-positive bacteria being 5.63 μg / mL.

9. The nanozyme according to claim 8, characterized in that: The bacteria include, but are not limited to, Escherichia coli and Staphylococcus aureus.

10. The nanozyme according to claim 1 is used in the pharmaceutical industry and chemical production fields.

Citation Information

Cited By

  • Selenium-copper nanoparticles based on polyvinylpyrrolidone modification and preparation method and antibacterial application thereof

    CN121081395A